Inductive Method for Evaluating RFID Security Protocols. (11th April 2019) - Liu, Defu; Yang, Guowu; Huang, Yong; Wu, Jinzhao
Abstract : Authentication protocol verification is a difficult problem. The problem of "state space explosion" has always been inevitable in the field of verification. Using inductive characteristics, we combine mathematical induction and model detection technology to solve the problem of "state space explosion" in verifying the OSK protocol and VOSK protocol of RFID system. In this paper, the security and privacy of protocols in RFID systems are studied and analysed to verify the effectiveness of the combination of mathematical induction and model detection. We design a (r, s, t)-security experiment on the basis of privacy experiments in the RFID system according to the IND-CPA security standard in cryptography, using mathematical induction to validate the OSK protocol and VOSK protocol. Finally, the following conclusions are presented. The OSK protocol cannot resist denial of service attacks or replay attacks. The VOSK protocol cannot resist denial of service attacks but can resist replay attacks. When there is no limit on communication, the OSK protocol and VOSK protocol possess (r, s, t)-privacy; that is to say they can resist denial of service attacks.